SHARIA CONTRACT IMPLEMENTATION IN PANYIURAN SHIP TRADING AT MUARA TEWEH PORT - akbar, wahyu; Khairunnisa; Zainal Arifin; Aufa, Naufatti (UIN Raden Mas Said Surakarta, 2025)
Trading is a lawful activity in Islam, requiring adherence to Sharia principles to ensure ethical and blessed business practices. Trade can occur through various mediums, including traditional markets, modern marketplaces, social media, and even merchant ships. Panyiuran ships serve as floating markets along the Barito River, Central Kalimantan, providing economic opportunities for traders and consumers in different villages. This study aims to analyze (1) the economic activities of traders on Panyiuran merchant ships, (2) the types of Sharia contracts applied in these trade transactions, and (3) the alignment of these activities with Islamic economic principles. This research employs a qualitative field study approach, utilizing purposive sampling to select participants, including three traders, one ship owner, one laborer, and three consumers. Data collection methods include observation, interviews, and documentation, analyzed through data reduction, presentation, and verification. Findings reveal that trade activities on Panyiuran ships resemble market transactions, with various goods being sold weekly in different locations. The applied Sharia contracts include Ijarah (rental agreements between traders and ship owners), Ujrah (wage contracts for laborers), and Ijab and Qabul (mutual consent in sales transactions). These activities comply with Islamic economic principles, particularly Muamalah Maddiyah and Muamalah Al-Adabiyyah, ensuring ethical trade practices.